Liver metastases of colorectal cancer contain different subsets of tissue-resident memory CD8 T cells correlated with a distinct risk of relapse following surgery - Syrine Abdeljaoued; Alexandre Doussot; Marie Kroemer; Emilien Laloy; Jean René Pallandre; Antoine El Kaddissi; Laurie Spehner; Myriam Ben Khelil; Adeline Bouard; Virginie Mougey; Ugo Chartral; Angélique Vienot; et al. (OncoImmunology)
Tissue-resident memory (TRM) T cells have emerged as key players in cancer immunosurveillance, and their presence has been linked to a favorable clinical outcome in solid cancer patients. Liver metastases exhibit a highly immunosuppressive tumor microenvironment, however, the role and clinical impact of TRM cell infiltration in colorectal cancer remain elusive. The expression of several tissue residency and activation biomarkers has been investigated on tumor-infiltrating lymphocytes isolated from 26 patients’ colorectal cancer liver metastases (CRC liver metastases) and compared to 16 peripheral blood samples of patients with CRC liver metastases. Cytokine production was also evaluated in in vitro-activated TRM and non-TRM cells. The prognostic value of TRM cells was also assessed in a well-defined cohort of CRC liver metastases. Here we identified two subsets of TRM cells expressing CD103 and/or CD69 showing significantly higher expression of tissue residency and activation biomarkers. CD103+CD69+ TRM cells subset showed almost exclusive expression of tumor reactivity biomarkers PD-1 and CD39. Supporting this observation, CD103+CD69+ TRM cells showed a more oligoclonal TCR repertoire. Both TRM subsets presented higher cytotoxic and functional capacity compared to non-TRM cells. Our study shows that only the presence of CD103+CD69+ TRM cells is associated with longer recurrence-free survival of colorectal cancer patients with liver metastases. Taken together, our work demonstrates the existence of a phenotypic heterogeneity of TRM cells in colorectal cancer liver metastases. In this study, we identified a population of CD103+CD69+ TRM cells exhibiting the characteristics of tumor reactivity and correlated with better patients’ prognosis, with potential implications in optimal therapeutic strategies determination.